Blood–brain barrier permeability in response to caffeine challenge. Issue 5 (26th June 2022) - Lin, Zixuan; Jiang, Dengrong; Liu, Peiying; Ge, Yulin; Moghekar, Abhay; Lu, Hanzhang
Abstract : Purpose: Caffeine is known to alter brain perfusion by acting as an adenosine antagonist, but its effect on blood–brain barrier (BBB) permeability is not fully elucidated. This study aimed to dynamically monitor BBB permeability to water after a single dose of caffeine tablet using a non‐contrast MRI technique. Methods: Ten young healthy volunteers who were not regular coffee drinkers were studied. The experiment began with a pre‐caffeine measurement, followed by four measurements at the post‐caffeine stage. Water‐extraction‐with‐phase‐contrast‐arterial‐spin‐tagging (WEPCAST) MRI was used to assess the time dependence of BBB permeability to water following the ingestion of 200 mg caffeine. Other cerebral physiological parameters including cerebral blood flow (CBF), venous oxygenation (Yv ), and cerebral metabolic rate of oxygen (CMRO2 ) were also examined. The relationships between cerebral physiological parameters and time were studied with mixed‐effect models. Results: It was found that, after caffeine ingestion, CBF and Yv showed a time‐dependent decrease ( p  < 0.001), while CMRO2 did not change significantly. The fraction of arterial water crossing the BBB (E) showed a significant increase ( p  < 0.001). In contrast, the permeability‐surface‐area product (PS), i.e., BBB permeability to water, remained constant ( p  = 0.94). Additionally, it was observed that changes in physiological parameters were non‐linear with regard to time and occurred at as early as 9 min after caffeine tablet ingestion. Conclusion: These results suggest an unchanged BBB permeability despite alterations in perfusion during a vasoconstrictive caffeine challenge.